Location Selection for Beekeeping in Optimizing Honey Production using Linear Programming Model (S/O 14038) - Abdul Rahman, Syariza; Benjamin, Aida Mauziah; Omar, Mohd Faizal (UUM, 2020)
Meliponiculture is an activity of raising stingless bees to obtain bee products, mainly honey. Honey production by bees varies depending on various factors which also affect its amount and quality. Meliponiculturists practiced beekeeping in many ways to maximise honey production and its quality such as by considering location of beekeeping, apiary, flowers and plants. Nevertheless, there are many criteria that should be considered in meliponicultures in analysing its importance in producing good quality and quantity of honey. As it involves multiple conflicting criteria, different multicriteria decision making (MCDM) techniques can be effectively applied to solve such type of problem. Furthermore, the suitability analysis of identified locations can be performed through GIS and efficiency of meliponiculture activities also can be assessed. Thus, this research applied MCDM techniques namely as Analytical Hierarchy Process (AHP), Fuzzy Analytical Hierarchy Process (FAHP) and Weighted Sum Method (WSM) to rank the criteria. A set of questionnaires with nine criteria is distributed to meliponiculturists. The criteria were selected based on previous studies and opinions from the experts. The criteria are (1) flowers and plants, (2) water and hydrology, (3) land features, (4) apiary, (5) human activities, (6) pest, (7) wind and humidity, (8) road network, and (9) temperature. Next, several locations of identified stingless bee farms were plugged into QGIS 3.8 to analyse its location suitability map and mathematical model is developed. A linear programming model namely as Data Envelopment Analysis was developed to calculate the efficiency score for each farm. Based on MCDM techniques, the results were analysed based on individual and group ranking. Both individual and group results provide a slightly different ranking by using the MCDM techniques. The location suitability analysis found that all the identified stingless bee farms support the findings in the MCDM phase and some are considered efficient in their honey production. This study provides an insight on the factors which affect the honey production and its quality in meliponiculture industry which could help optimizing the honey production. Findings from this research could help the Malaysian Agricultural Research and Development Institute (MARDI) in educating the commercial beekeeping to increase their honey production and assessed their production efficiency.